Undetectable? Looking for urban traces of HIV/AIDS in Montréal’s gay Village (Medicine Anthropology Theory, 2020)
In recent years, the ‘end of AIDS’ has been at the top of the international scientific and political agenda. At the same time, attention to the dark years of the epidemic is increasing, revealing a form of nostalgia for a time of collective mobilization. But what is to be said of the current state of the disease, between the nostalgia for a tragic past and the hope of a world without AIDS? This think piece was prompted by the increasing erasure of contemporary experiences of the sickness. At a time when we have the means to render HIV biologically undetectable, I propose to explore another of the virus’s materialities: its social and historic inscription in urban settings, in particularly in Montreal’s gay neighbourhood.